(untitled) (Advancements in Homeopathic Research, 2022)
Androgenetic alopecia (AGA) is the most common type of baldness characterized by progressive hair loss. AGA has always affected the patients psychologically. AGA can produce negative impact on quality of life of such patients. Homoeopathic literature shows that cases of alopecia have been successfully treated with homoeopathic medicines. This is a case of 28-year old man with androgenetic alopecia. The patient was treated with individualised homoeopathic medicine over a period of 17 months.There was a significant improvement with homoeopathic treatment, regrowth of hair in the bald area without any recurrence.